Influence of Consumers’ Self Perception on Devaluation of Ugly Produce – Marketing Strategies to Reduce Food Waste in the Indian Context - Saldanha, Avil Terrance; Aranha, Rekha (Indian Journal of Marketing, 2022)
Ugly produce refers to aesthetically imperfect fruits and vegetables and also fruits and vegetables with minor blemishes. Ugly produce does not refer to spoilt, rotten, or germ-infected fruits and vegetables. The basic premise of this study is from self-signaling and self-perception theories. The self-signaling theory states that when people make a choice, they disclose something of their character and personality not just to others, but also to themselves. Self-perception theory (SPT) developed by psychologist Daryl Bem asserts that people develop their attitudes by observing their own behavior and further concluding what attitudes must have caused it. Classically, consumers undervalue ugly produce because of altered self-perceptions; simply visualizing the consumption of imperfect produce acts as a self-indicative signal that negatively affects how consumers view themselves. Due to this, the unattractive produce, even though perfectly edible and with the same taste and nutritional value, is rejected by consumers merely based on shape or some other cosmetic blemish. We discussed the strategies adopted by Indian startups and organizations to reduce food waste. Deep discounting is the strategy followed by food retailers worldwide to sell ugly produce, however, this is not the best strategy as it leads to losses for both the retailers as well as the farmers. We suggested alternative strategies successfully followed by foreign retailers, such as spreading awareness, boosting self-confidence and esteem among consumers, attracting kids, etc., which can be followed by Indian food retailers for selling ugly fruits and vegetables.